An alternative scaling factor in quasi-newton methods for uncostrained optimization - Muhammad Fauzi Embong (Terengganu: Universiti Malaysia Terengganu, 2012)
Quasi-Newton methods play a vital role in theoretical and computational mathematics. The first quasi-Newton algorithm was developed by Davidon in mid 1950s, and later demonstrated by Fletcher and Powell that the new algorithm was more reliable and faster than the existing methods.